Autonomous Trajectory Control for Directional Drilling - Panchal, Neilkunal (Cranfield University, 2013)
The demand on the world's energy resources will intensify as the prediction of the global population rising by 2.3 billion by 2050 becomes a reality. With more than half of the worlds energy consumption being currently derived from oil and gas, there is a need to access challenging new reserves of which there is an estimated 5.5 trillion barrels remaining. The need, therefore, to develop and employ more sophisticated methods to extract these hard to-reach reserves is clear. Rotary steerable drilling with near-bit sensors, actuators, and processors will play a significant role in accessing this oil, having already reduced the time and extended the reach of wellbores. In addition to this, trajectory control can further enhance the capability of a rotary steerable system, reducing costs and improving the hydrocarbon recovery volume in the oilfield development process. This thesis presents a general system of trajectory control consisting of three subsystems: a subsystem for generating optimum geometric well-plan profiles through target volumes in the reservoir; a subsystem for stabilizing the propagating attitude of the centre-line of the borehole; and a subsystem for generating optimum attitude set-points for the downhole attitude control system for executing the well-plan. The attitude control system, determines the attitude represented as a unit vector from on-board sensors located near the drill-bit. The control action is represented as an axis which rotates the attitude of the steering assembly towards the demand attitude along an arc of a great circle in the attitude state-space. This method is extended further to investigate the effect of spatially delaying the attitude sensors behind the drill-bit on the attitude tracking. This sensor-to-bit distance induces spiraling in the profile of bore hole. This motivated an extension to the attitude control system whereby the feedback control law acts on the predicted attitude at the bit. The well-planning methodology generates paths continuous in their posi tion, direction, and curvature in a multi-objective optimization strategy. The solution is a b-spline space-curve minimizing a weighted sum of ar clength, strain energy and torsion objective functions. The absolute curva ture is constrained, ensuring that wells are planned with respect to the cur vature capability of the steering assemblies. These well-plans are comprised of a concatenation of smaller well-plans between targets in a hydrocarbon reservoir. These targets are represented as a combination of equality and inequality constraints on the position and attitude. The trajectory control strategy determines a correction well-plan coincident with the measured position and attitude of the steering assembly to guide the borehole towards the well-plan. This correction path is represented as a b-spline space curve which minimizes a weighted sum of wellbore tortuosity and well-plan deviation with respect to the curvature constraint of the steer ing assembly. The integrated system of the attitude and trajectory control is demonstrated in simulation to guide a modeled 8◦/100ft push-the-bit tool to converge towards and track a 2◦/100ft well-plan to an accuracy of 0.5m. The commercial value of the system for the oilfield services industry is in vestigated through a market analysis for rotary steerable systems leading to a proposition of value. Reducing hole-spiraling through attitude control systems reduces the friction in the well-bore on the drill-string and casing liners extending the depth capability of well-bores. This allows greater cov erage of hydrocarbon volumes to be accessed from a single platform, thereby reducing the number of platforms required in an oilfield development pro gramme. Extending the reach of a well increases the production volume from a single well by increasing the footage contact with hydrocarbon sat urated rocks. The value in introducing a trajectory control system, by minimizing well-plan deviation reduces costs associated with sidetracking a well. Furthermore the benefit of integrating a well-plan deviation minimiz ing trajectory control system with existing rate of penetration optimization technologies has scope to reduce rig time where it is estimated that there is a global annual benefit of USD490m.
Keywords: drilling; trajectory control systems; oil and gas industry; attitude sensors